Between Light and Shadow: Angels, Satan, and Jinn in Islamic and Christian Perspectives - Thobias, Boy Swingly Freny; Ndraha, Happy Daud; Tetty, Daniel Edward; Hasugian, Doni (PT FORMOSA CENDEKIA GLOBAL, 2025)
The study of angels, demons, and jinn is a crucial theme in both Islamic and Christian theology, as it relates to faith, religious practices, and socio-cultural perceptions. This research employs a qualitative method through library research and a comparative approach, using the Qur’an and the Bible as primary sources, supported by classical commentaries of Ibn Kathir and Matthew Henry, along with academic works on demonology. The findings reveal that in Islam, angels are understood as obedient spiritual beings, demons originate from rebellious jinn, and jinn themselves are creatures with free will. In contrast, Christianity views angels as God’s messengers, demons as fallen angels, while the concept of jinn aligns more closely with evil spirits. These differences influence not only theology but also spiritual practices, popular culture, and interfaith dialogue.